Pembentukan Karakter Mempengaruhi Pendidikan Anak - Fathiyah Ikhsani Siregar; Rahmatul Zikri Amalia; Gusmanelli Gusmanelli (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The family environment is the main factor in forming a child's character. This research analyzes the role of the family in instilling moral and social values ​​in children. By using library research methods, this research aims to make adults, especially parents, aware that consistent parenting patterns, open communication, and providing good examples by parents greatly contribute to the development of children's character. This research highlights the importance of family and school collaboration in efforts to form a young generation with character. And the digital era has brought significant changes to the educational process. Apart from the role of the environment and family, this research also analyzes the influence of technology on the formation of children's character. Unwise use of technology can have a negative impact on a child's character development, such as a tendency towards individualism and a lack of empathy. However, the proper use of technology can be an effective tool in instilling positive values ​​in children. This research suggests the importance of digital literacy and adequate assistance for students in using technology.